Web Tutorial in Reactive and Neoplastic Lymph Node Pathology (Out of Print) - David Weissmann (Association of American Medical Colleges, 2007)
Abstract This web-based resource is an extensive tutorial on lymph node pathology. Topics covered in this resource include both non-Hodgkin and Hodgkin lymphomas, plasmacytomas, and both normal and benign lymph nodes. Supplemental information about immunophenotyping and molecular pathology is also provided. The site includes explanations of lymphoma classification and descriptions of such ancillary techniques as flow cytometry. The website is copiously illustrated with numerous gross and microscopic images/diagrams. Links to additional hematopathology resources are also provided.